The impact of human capital on the sustainable development of regions in the context of creative formations - Chzao Nin; V. S. Shkarina (Интеллект. Инновации. Инвестиции, 2025)
The aggravation of the economic situation has actualized the need to study the formation of a model of sustainable development of regions. Since the second half of the twentieth century, the transition from an industrial to a post-industrial type of economy has begun in the developed countries of the world. One of the signs of such a transformation was the relocation of most industrial enterprises from Western European countries to countries with cheaper labor, optimal climatic and economic conditions. Among the consequences of such changes are the following: a change in the structure of the labor force and employment, manifested in a reorientation to the service sector; a change in the structure of costs and the specifics of consumption. Currently, the cost of production is 20% of the price, while 80% is marketing expenses. The modern economic system is characterized as a «club economy», and the consumption of certain goods is becoming an element of mass communication and a way to minimize transaction costs. Entire industrial areas are disappearing, and there is a massive population displacement. At the same time, unemployment is rising in previously developed industrial regions.